Effects of pandemics uncertainty on fertility - Wang, Yonglong; Gozgor, Giray; Lau, Chi Keung Marco (Frontiers in Public Health, 2022)
The COVID-19 pandemic has affected various dimensions of the economies and societies. At this juncture, this paper examines the effects of pandemics-related uncertainty on fertility in the panel dataset of 126 countries from 1996 to 2019. For this purpose, the World Pandemics Uncertainty Indices are used to measure the pandemics-related uncertainty. The novel empirical evidence is that pandemics-related uncertainty decreases fertility rates. These results are robust to estimate different models and include various controls. We also try to explain why the rise in uncertainty during the COVID-19 pandemic has resulted in the fertility decline.